(untitled) (PIONIR: JURNAL PENDIDIKAN, 2020)
The covid 19 pandemic exposes universities to be able to carry out the learning process online. This is a challenge for PGMI lecturers to prepare appropriate teaching materials and strategies in order to be able to improve students’ analytical skills in understanding online lecture material. The purpose of this study was to determine the problem analysis skills of PGMI IAIN Lhokseumawe students in the online learning process during the Covid 19 pandemic and student responses to the implementation of online learning during the Covid 19 pandemic. This study used descriptive qualitative research methods with the subject of second semester students of PGMI IAIN Lhokseumawe, data collection was carried out through interviews, observation and documentation study. From the research results, it was found that the majority of students already had good analytical skills where the results of the interviews revealed that students had been able to choose important material concepts and identify them into sub-material so that they were easy to understand. Students’ analytical skills cannot be separated from the role of lecturers in choosing strategies and preparing appropriate learning media and being able to use information technology well. It can be concluded that the analytical skills of PGMI students in online learning look better. This can be seen from the student’s ability to analyze problems with the lecture material given, namely being able to transform information and connect the material with real conditions in learning at MI.